Primerjava dostopa do rehabilitacije za bolnike z amiotrofično lateralno sklerozo v različnih državah - Jedlička, Željko (Rehabilitacija (Ljubljana), 2016)
Background: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease with predominant impairment of motor neurons. Patients with ALS involved in the multidisciplinary care have a better survival and report higher quality of life. Patient's close ones and patients' organisations are an important part of the multidisciplinary health care of the patients with ALS. As the disease progresses, the patient needs more and more walking and mobility aids, aids for daily living, communication aids, and breathing and respiratory aids. We wanted to find out how available is the access to a multidisciplinary team, medical aids, and social/financial assistance for patients with ALS in different countries. Methods: We designed a questionnaire with questions on the accessibility to multidisciplinary team, medical aids and social/financial compensations. The questionnaire was sent to associations of patients with ALS through the International Alliance for ALS/ BMN. Results: Completed questionnaires were received from 8 of 44 (18 %) of national associations of patients with ALS (from Germany, Australia, England, Ireland, Spain, Turkey, USA, Israel and Slovenia). All the completed questionnaires were included in further analysis. Differences in access to multidisciplinary team and medical aids were found to be small. Patients with ALS have access to the rehabilitation team in all the studied countries, but the teams are not complete everywhere and/or access might be limited. Different medical aids for patients with ALS do not affect the functioning and quality of life of patients equally. We noted the discrepancy between the patients' ratings of usefulness and satisfaction with various medical aids on one hand and access to them on the other hand. The respondents reported the long time to delivery of medical aids as a significant problem. Major differences between countries exist in the payment of the multidisciplinary team, medical aids and especially the social support for patients with ALS. Conclusions: Patient advocacy organisations should devote their attention to achieving and balancing the social and economic rights for patients with ALS, supporting access to proper medical aids, reducing the time of delivery of medical aids and supporting access to the rehabilitation programs and a standardized multidisciplinary treatment. These endeavours are in line with the international clinical guidelines of care for patients with ALS. The desired changes are important, yet neither complex nor difficult to achieve.
Keywords: amiotrofična lateralna skleroza; Amyotrophic lateral sclerosis; bolniki; medical aids; nacionalna združenja; national associations; Patients; pripomočki